Paid Parental Leave Lessons from OECD Countries and Selected U.S. States - Adema, Willem (OECD Social, Employment and Migration Working Papers, 2015)
The United States is at a crossroads in its policies towards the family and gender equality. Currently America provides basic support for children, fathers, and mothers in the form of unpaid parental leave, child-related tax breaks, and limited public childcare. Alternatively, the United States' OECD peers empower families through paid parental leave and comprehensive investments in infants and children. The potential gains from strengthening these policies are enormous. Paid parental leave and subsidised childcare help get and keep more women in the workforce, contribute to economic growth, offer cognitive and health benefits to children, and extend choice for parents in finding their preferred work-life strategy. Indeed, the United States has been falling behind the rest of the OECD in many social and economic indicators by not adequately investing in children, fathers and mothers